Performance Improvement Incremental Conductance Algorithm using Incremental Fuzzy to Reach GMPP under Partial Shading Conditions - Imam Sutrisno; Joessianto Eko Poetro; Pranowo Sidi; Boedi Herijono; Antonius Edy Kristiyono; Monika Retno Gunarti (International Journal of Marine Engineering Innovation and Research, 2024)
This paper proposes an improved Maximum Power Point Tracking (MPPT) algorithm for photovoltaic (PV) systems under partial shading conditions. The proposed method enhances the widely used Incremental Conductance (IC) algorithm by incorporating an incremental fuzzy control technique. The conventional IC algorithm suffers from limitations in adapting to rapidly changing irradiation conditions due to its fixed step size. The proposed Inc-Fuzzy algorithm dynamically adjusts the step size based on the change in power and voltage, enabling it to better track the Global Maximum Power Point (GMPP) under partial shading. Simulation results demonstrate that the Inc-Fuzzy algorithm achieves an average accuracy of 98.29% under constant irradiation and outperforms the conventional IC algorithm by 1.69% in terms of captured power during sudden irradiation changes. This improvement highlights the effectiveness of the Inc-Fuzzy approach in enhancing the performance of MPPT for PV systems under challenging operating conditions.